2019
DOI: 10.1159/000499144
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Neurodevelopmental Trajectories: Role of Maternal and Early-Life Nutrition

Abstract: Pregnancy and early life are characterized by marked changes in body microbial composition. Intriguingly, these changes take place simultaneously with neurodevelopmental plasticity, suggesting a complex dialogue between the microbes that inhabit the gastrointestinal tract and the brain. The purpose of this chapter is to describe the natural trajectory of microbiota during pregnancy and early life, as well as review the literature available on its interaction with neurodevelopment. Several lines of evidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 151 publications
(153 reference statements)
0
28
0
1
Order By: Relevance
“…Although the role of maternal nutrition in programming of the offspring metabolic, immune and nervous system development has been well documented in humans and food-producing animals including cattle (Palmer, 2011; Caton et al, 2019), the potential involvement of the maternal microbiome in the developmental origins of health and disease has recently began to be better appreciated (Stiemsma and Michels, 2018; Calatayud et al, 2019; Codagnone et al, 2019). It was hypothesized that undesired alterations in the maternal microbiota could indirectly influence fetal development, and that these effects may subsequently be transmitted to progeny, resulting in the development of an altered microbiota in offspring (Calatayud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of maternal nutrition in programming of the offspring metabolic, immune and nervous system development has been well documented in humans and food-producing animals including cattle (Palmer, 2011; Caton et al, 2019), the potential involvement of the maternal microbiome in the developmental origins of health and disease has recently began to be better appreciated (Stiemsma and Michels, 2018; Calatayud et al, 2019; Codagnone et al, 2019). It was hypothesized that undesired alterations in the maternal microbiota could indirectly influence fetal development, and that these effects may subsequently be transmitted to progeny, resulting in the development of an altered microbiota in offspring (Calatayud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of maternal nutrition in programming of the offspring metabolic, immune and nervous system development has been well documented in humans and food-producing animals including cattle (Palmer, 2011;Caton et al, 2019), the potential involvement of the maternal microbiome in the developmental origins of health and disease has recently began to be better appreciated (Stiemsma and Michels, 2018;Calatayud et al, 2019;Codagnone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the maternal microbiome in obese women is altered, and specifically excessive weight gain in pregnancy can further change the microbiome (106). Whole brain effects of the maternal obese microbiome are noted, by assessing overall behavior of animals born to obese mothers (107) (for a review see (108)). Recently, it was reported that reconstituting the microbiome of offspring born from obese mothers, is sufficient to reverse known social deficits in these animals (109).…”
Section: Microbiomementioning
confidence: 99%
“…Compared to GI homeostasis, more surprising is the association between microbiota and brain function, and the fact that the intestinal flora modulates immune, endocrine, and neuroendocrine maturation in nervous system sprouting. Colonization of the human gut upon birth is important for neonatal brain development, since it allows the synthesis of vitamins and fatty acids, regulation of BDNF (Brain-derived neurotrophic factor), synaptophysin and PSD-95 (177). Experimentally, sterile mice elicit decreased expression of BDNF in the cerebral cortex and hippocampus, and they show signs of anxiety and less activity performance (178); while another study shows that recolonization with healthy flora permitted production of different neurotransmitters (NTs) and the abolition of anxiety symptoms (179).…”
Section: Microbiota In Pdmentioning
confidence: 99%